Role of Exosomal Non-coding RNAs in Gastric Cancer: Biological Functions and Potential Clinical Applications - Hu, Feng; Liu, Jixuan; Liu, Huibo; Li, Fan; Wan, Minjie; Zhang, Manli; Jiang, Yanfang; Rao, Min (Frontiers in Oncology, 2021)
Gastric cancer (GC) is one of the most common fatal cancers worldwide. The communication between GC and other cells in the GC microenvironment directly affects GC progression. Recently, exosomes have been revealed as new players in intercellular communication. They play an important role in human health and diseases, including cancer, owing to their ability to carry various bioactive molecules, including non-coding RNAs (ncRNAs). NcRNAs, including micro RNAs, long non-coding RNAs, and circular RNAs, play a significant role in various pathophysiological processes, especially cancer. Increasing evidence has shown that exosomal ncRNAs are involved in the regulation of tumor proliferation, invasion, metastasis, angiogenesis, immune regulation, and treatment resistance in GC. In addition, exosomal ncRNAs have promising potential as diagnostic and prognostic markers for GC. Considering the biocompatibility of exosomes, they can also be used as biological carriers for targeted therapy. This review summarizes the current research progress on exosomal ncRNAs in gastric cancer, focusing on their biological role in GC and their potential as new biomarkers for GC and therapeutics. Our review provides insight into the mechanisms involved in GC progression, which may provide a new point cut for the discovery of new diagnostic markers and therapeutic strategies.